‘Cool! and creepy’: engaging with college student stakeholders in Michigan’s biobank - Platt, Tevah (Springer Berlin Heidelberg, 2014)
Large population biobanks, important resources for genomic research, also present ethical challenges. The Michigan BioTrust for Health makes dried bloodspots (DBS) leftover from newborn screening, including ~4.5 million collected before 2010 without written consent, available for health research. Absent prospectively gathered consent and/or current engagement with 18- to 29-year olds, little is known about opinions and beliefs from this age group about use of the bloodspots for research. We engaged 2,101 students—BioTrust participants and their peers—at information booths at 20 college campuses across the state to educate youth about the BioTrust and gather information about consent preferences and about hopes and concerns about this public health program. We surveyed student stakeholder DBS research consent preferences and fielded a “postengagement” survey to gauge the attitudes of participants and to evaluate the campus engagement. The most prevalent themes in open-ended comments were support for biobank research and concern that Michiganders are not aware of their participation. While 78 % of students said they would, if asked, opt in to the BioTrust, half of these preferred to be contacted each time a researcher sought to use their DBS. Students reported great interest in the topic and strong likelihood to share what they had learned. BioTrust participants are interested in learning about their role in an initiative whose goals they widely support. Public engagement is particularly important to biobank participants who, absent traditional consent practices, are unaware of their participation. Health-fair style engagements were effective for targeting college-aged stakeholders, communicating complex messages, and likely increasing knowledge. Retrospective biobanks and biobanks that collect proxy consent need policies to respect those who would opt out and will need resources to educate participants and conduct community outreach that is a safeguard to public trust. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-014-0190-4) contains supplementary material, which is available to authorized users.